2017
DOI: 10.1016/j.dental.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and properties of a dental adhesive functionalized with polyhedral oligomeric silsesquioxanes (POSS) and bioactive glass

Abstract: Multifunctional POSS may be incorporated into dental adhesives to provide a bioactive potential without changing material properties adversely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 39 publications
6
44
0
12
Order By: Relevance
“…BAG Among bioceramics, BAG is a relatively new material which has been incorporated into dental resin composites and adhesives. A total 20 studies [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] was found as per the inclusion criteria, whereby seven studies 92,[94][95][96]98,106,108) were based on fluoride-based bioactive glass (F-BAG). Few studies showed doping of zinc 101,102,107) , silver 110) , and niobiophosphate 109) in BAG powders.…”
Section: Acpmentioning
confidence: 99%
“…BAG Among bioceramics, BAG is a relatively new material which has been incorporated into dental resin composites and adhesives. A total 20 studies [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] was found as per the inclusion criteria, whereby seven studies 92,[94][95][96]98,106,108) were based on fluoride-based bioactive glass (F-BAG). Few studies showed doping of zinc 101,102,107) , silver 110) , and niobiophosphate 109) in BAG powders.…”
Section: Acpmentioning
confidence: 99%
“…Each specimen was evaluated at a wavelength range of 500–4,000 cm −1 , a resolution of 4 cm −1 , and with 32 scans. A thin layer of PUDMA X or adhesive (5 mm diameter, 0.25 mm thick, n = 5) was applied onto a potassium bromide pellet, then evaluated using an FTIR spectrometer with spectra ranging from 900 to 4,000 cm −1 , as described previously . The specimens containing FL and SB2 adhesives were light‐cured for 20 and 10 s, respectively, as recommended and without solvent volatilization.…”
Section: Methodsmentioning
confidence: 99%
“…Though mono-functional POSS particles resulted in a highly declined conversion and bioactive glass particles strongly enhanced the viscosity, apparently, their application in dental adhesives is limited to specic uses and substances. 184 Tooth whitening agents were necessarily nano-modied to increase the whitening efficiency and decrease their harmful side effects. For example, calcium peroxide nanoparticles could penetrate deeper into the tooth structure through micro and nano cracks, make longer surface contact, and increase the effectiveness of the whitening agent.…”
Section: Nano-materials For Restorationmentioning
confidence: 99%